PROBLEMATIKA GURU DALAM MENGATASI KESULITAN MEMBACA LANCAR PADA SISWA KELAS IV SDS TARBIYATUL ISLAM SAMBAS TAHUN PELAJARAN 2025/2026 - Minarsih; Asyruni Multahada; Effiyadi (CV. ADIBA ASIHA AMIRA, 2026)
This study aimed to analyze and describe: (1) the fluent reading difficulties experienced by fourth-grade students at Tarbiyatul Islam Elementary School (SDS Tarbiyatul Islam) Sambas during the 2025/2026 academic year; (2) the challenges encountered by teachers in assisting fourth-grade students in overcoming fluent reading difficulties; and (3) the strategies implemented by teachers to improve students' fluent reading skills.This study employed a qualitative approach with a descriptive research design. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using the interactive model of data analysis, which consisted of data collection, data reduction, data display, and conclusion drawing. To ensure the trustworthiness of the findings, data triangulation and member checking were employed. The findings revealed that: (1) fourth-grade students experienced several fluent reading difficulties, including hesitant reading, mispronunciation of letters and words, inappropriate intonation, slow reading speed, and limited reading comprehension. These difficulties were influenced by both internal factors, such as low reading interest and motivation, and external factors, including limited parental support and insufficient access to reading materials. (2) Teachers encountered several challenges in addressing students' fluent reading difficulties, including limited instructional time, considerable differences in students' reading abilities, less effective instructional methods, and low parental involvement in supporting students' learning at home. (3) To address these difficulties, teachers implemented various strategies, including individualized reading guidance, repeated reading practice, the use of simple instructional media such as word cards, motivational support, and regular read-aloud activities in the classroom. These strategies were intended to enhance students' reading fluency, accuracy, and comprehension, thereby contributing to their overall academic achievement.